English for Nursing Students Based on Task-Based Learning - Ahmad Rusli; Jufrizal Jufrizal; Hamzah Hamzah (Postgraduate School, Universitas Negeri Padang, 2019)
The aim of this research was to develop English learning materials based on task-based learning in the form of handout for nursing study program students at STIKES Aufa Royhan Padangsidimpuan. In the development process, this research used to: 1) identify the needs of teaching/learning Englishof the students; 2) develop English learning materials based on task-based learning; 3) find out the experts’ judgments about the developed handout; 4) find out the users’ perceptions about the developed handout. Research method was Research and Development (R&D). ADDIE model used to develop the handout. The result of needs analysis indicated the students needed to learn English language use in the nursing context. Then appropriate handout of English for Nursing was developed based on the result of needs analysis. Based on the experts judgments and users’ perception, the developed handout are categorized valid, effective, and practical.